Free help with homework

Why join Brainly?

  • ask questions about your assignment
  • get answers with explanations
  • find similar questions


1-2a -2b -3(a+b)²
= 1-2(a+b)-3(a+b)²
=1- 3(a+b) +(a+b) -3(a+b)²
0 0 0
let y=a+b
1-3y +y-3y ²
=(1-3y) y(1-3y)
=(1-3a-3b) (1+a+b) 

0 0 0
plz mark brainlest
dont equate it with zero, it's expression not equation
The Brain
  • The Brain
  • Helper
Not sure about the answer?
Learn more with Brainly!
Having trouble with your homework?
Get free help!
  • 80% of questions are answered in under 10 minutes
  • Answers come with explanations, so that you can learn
  • Answer quality is ensured by our experts